То the synchronous work of pulsed sources of seismic waves - S. P. Ekomasov (Известия высших учебных заведений: Геология и разведка)
Researches have been made with the use of a hydropneumatic source of seismic waves. This source on the realized efforts of the shock interaction with a soil half-space considerably exceeds all known designs of radiators (sources) of pulse type. In this regard it shows higher seismic efficiency. The most important characteristic of the work of the pulse sources of seismic waves is a stability of the response time — a time interval from the moment of giving of a signal for producing of the blow until the very blow. Only with the achievement of the necessary stability the work in the mode of grouping of sources and accumulation of signals is possible. Features of the formation of response time of a hydropneumatic source are given. The analysis of the assessment of the parameters of synchronism of the pulse sources is made by a modem control system of their work. An influence of the rigidity of the soil on the assessment of stability of the response time and synchronism is shown. The system of the assessment of the stability used in the existing pulse sources at its application does not reflect the actual stability of response time in the radiators possessing a big force of blow.